Step Up to IELTS : - Jakeman, Vanessa (Cambridge University Press, 2004)
Step Up to IELTS covers essential exam skills and language for IELTS in approximately sixty hours of teaching time, and familiarises students quickly with the exam. The course covers both the Academic and General Training modules. Shorter, achievable exam-type tasks build students' exam skills, before students try the more challenging tasks at authentic test level.